Energy consumption for water use cycles in different countries: A review. (15th September 2016) - Wakeel, Muhammad; Chen, Bin; Hayat, Tasawar; Alsaedi, Ahmed; Ahmad, Bashir
Highlights: Energy consumptions for water use recycles in different countries were investigated. Different case studies in context of energy-water nexus were reviewed. Various models for energy consumption in water sector were examined. Abstract: Energy and water are essential, inseparable, and inextricably linked resources that are recognized as indispensable inputs to modern economic and national security. Understanding the nexus of energy and water may help minimize energy and water consumption and reduce environmental emissions. This paper presents a literature review of the current status, research gaps, dependence factors, and possible improvement measures to reduce energy consumption in the water sector. The energy use in the extraction, desalination, pumping, collection, and wastewater treatment stages of the water sector from a global perspective in various developed and developing countries is investigated. The results show that water supply and wastewater services are energy intensive globally owing to old infrastructures and technologies. Energy intensities in the water sector vary with technology, geographical distances, and demographic conditions. The methodologies for energy accounting for various water uses are also summarized. Finally, knowledge gaps, challenges and policy implications are identified by synthesizing previous research.